MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATERI SIFAT-SIFAT WAJIB BAGI ALLAH DENGAN METODE MAKE A MATCH - NENENG AISYAH (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2023)
This Classroom Action Research (PTK) discusses the use of make a match learning methods in the teaching and learning process of Aqidah Akhlak subjects. This research is motivated by the low activity conditions and learning outcomes of grade 7.7 students, especially in the material of mandatory, impossible and jaiz properties for Allah in the Aqidah Akhlak subject at MTs Negeri 1 Bekasi for the 2021-2022 academic year. For that we need a learning model that can increase the activity and student learning outcomes in the material. Data collection was carried out by means of interviews, observation and documentation at MTs Negeri 1 Bekasi. The results of this study indicate that the activities and learning outcomes in the material are mandatory, impossible and jaiz for Allah in the Aqidah Akhlak subject for class 7.7 MTS Negeri 1 Bekasi TP. 2021-2022 which was previously considered low actually increased after the use of the make a match learning method. This is evident from the acquisition of scores that reached KKM, which was originally 30%, to 90%. ABSTRAKPenelitian Tindakan Kelas (PTK) ini membahas tentang penggunaan metode pembelajaran make a match dalam proses belajar mengajar mata pelajaran Aqidah Akhlak. Penelitian ini dilatarbelakangi oleh kondisi aktivitas dan hasil belajar siswa kelas 7.7 yang rendah khususnya pada materi sifat-sifat wajib, mustahil dan jaiz bagi Allah mata pelajaran Aqidah Akhlak MTs Negeri 1 Bekasi tahun pelajaran 2021-2022. Untuk itu diperlukan suatu model pembelajaran yang dapat meningkatkan aktivitas dan hasil belajar siswa pada materi tersebut. Perolehan data dilakukan dengan cara wawancara, observasi dan dokumentasi di MTs Negeri 1 Bekasi. Hasil penelitin ini menunjukkan bahwa aktivitas dan hasil belajar pada materi sifat-sifat wajib, mustahil dan jaiz bagi Allah mata pelajaran Aqidah Akhlak siswa kelas 7.7 MTS Negeri 1 Bekasi TP. 2021-2022 yang sebelumnya dinilai rendah ternyata meningkat setelah digunakannya metode pembelajaran make a match. Terbukti dari perolehan nilai yang mencapai KKM yang asalnya 30% menjadi 90%.